Protein-iron interaction using cyclic voltammetry - Saiful Irfan Mohamed Bajuri (2019)
Across all industries, companies are continuously searching for methods to increase productivity and to save costs by reducing machine downtime and maintaining equipment at high standards. In marine and offshore industries specifically, significant amount of downtime cases occur because of metal structural failure due to corrosion, when there is a possible interaction between a protein and metal. Most of these metal structures contain iron. However, due to the complexity of any protein based reaction, phenomenon of protein-iron is generally still poorly understood. Herein, the author uses an electrochemical set up called Cyclic Voltammetry to quantify any kind of favourable protein-iron interaction. A commonly investigated protein, lysozyme was used. This report documents the effects of changing the following variables: scan rate ranging from 100mV/s to 250mV/s, scan limit, presence of degassing, concentration of metal, concentration of protein, and type of electrodes used from glassy carbon (GC), gold, edge plane pyrolytic graphite (EPPG) electrodes as they may affect protein-iron interaction. The results show that cathodic and anodic peaks in CV were observed using EPPG electrode due to its high sensitivity, but no conclusive results were detected using GC and gold electrodes. CV of FeCl added to lysozyme (when FeCl is limiting in quantity) indicated higher current peaks when compared with the respective FeCl control solution, whereas CV shape of FeCl in excess to lysozyme showed a similar graph to FeCl control solution. A faster scan rate of 250mV/s also showed clearer peaks compared to slower scan rates of 100mV/s. Based on these key findings and improvement that could be done on the work, the authors have suggested future work that could shed light into the poorly understood phenomenon: protein induced corrosion (PIC).